Vascularized, Denervated Muscle Targets: A Novel Approach to Treat and Prevent Symptomatic Neuromas. Issue 4 (21st April 2020) - Tuffaha, Sami H.; Glass, Connor; Rosson, Gedge; Shores, Jaimie; Belzberg, Allan; Wong, Alison
Abstract : Summary: There are many surgical approaches described to treat and prevent symptomatic neuromas, each of which has significant limitations. Here we describe the rationale and technical approach for a novel method that carries the promise of addressing some of these limitations.